آثر تمرینات إدراكیة مھاریة في تنمیة إدراك الإحساس بالمسافة لمھارة المناولة بكرة الید لأعمار (١٣ ـ ١٤ (سنة - احمد مھدي صالح (مجلة الفتح للبحوث التربوية والنفسية, 2023)
الملخص إن للأخطاء المھاریة أسباب عدة یكون أحدھا فقدان الإحساس ببعض المدركات الحسیة ومنھا إدراك الإحساس بالمسافة لمھارة المناولة والاستلام بكرة الید لأعمار ١٣ـ١٤ سنة ، لذا أراد الباحث دراسة ھذه المشكلة . وقد ھدفت الدراسة إلى إعداد تمرینات إدراكیة مھاریة والتعرف على آثرھا في تنمیة إدراك الإحساس بالمسافة لمھارة المناولة والاستلام لأعمار ١٣ـ١٤ سنة بكرة الید . وقد استخدم الباحث المنھج التجریبي ذو تصمیم المجموعتین الضابطة والتجریبیة ذات الاختبارین القبلي والبعدي على عینة من (٦٠ (طالب بأعمار (١٣ـ١٤ (سنة .وقد استنتج الباحث بأن التمرینات الإدركیة المھاریة قد ساھمت في تنمیة إدراك المسافة لمھارة المناولة والاستلام بكرة الید . Preferred to exercise skill in the development of cognitive perception sense of the distance to the skill of handling reel hand for ages (13-14) By Ahmed Mahdi Saleh PHD student / basic education college /university of Diyala Abstract The technique errors several reasons be one of loss of sensation to some perceptions, including recognizing the sense of distance to the skill of handling and receiving hand reel for ages 13-14 years, so the researcher wanted to study this problem. The study aimed to develop skill and cognitive exercises to identify their impact in the development of understanding the sense of the distance to the skill of the receipt and handling for ages 13-14 years reel hand. The researcher used the experimental approach with the design of the experimental and control groups with pre and post tests on a sample of 60 students ages (13-14) years. Researcher has concluded that exercise Aladrickah the technique has contributed to the development of awareness of the distance to the skill of handling and receiving hand reel